Effect of connection mode and mass flux on the energy output of a PVT hot water system. (December 2017) - Yuan, Yanping; Ouyang, Liping; Sun, Liangliang; Cao, Xiaoling; Xiang, Bo; Zhang, Xingxing
Highlights: Model for PVT system of various connection modes was developed and validated. Effect of connection mode and mass flux has been investigated comprehensively. Variations in temperature and energy output under different conditions were studied. Optimum connection mode and mass flux were N  = 2 and 0.035 kg·m −2 ·s −1, respectively. Abstract: The connection mode and mass flux are critical that significantly influence the performance of photovoltaic thermal (PVT) hot water systems. However, comprehensive research on the effect of connection mode and mass flux on the energy output of a PVT hot water system has not been reported. A PVT hot water system with five connection modes containing the number collectors in series N  = 1, 2, 3, 4, and 6, as well as mass flux ranging from 0.01 kg·m −2 ·s −1 to 0.04 kg·m −2 ·s −1 was developed. The corresponding dynamic heat transfer model of the PVT hot water system was also programmed in FORTRAN. The results indicate that: (1) The power output of the N  = 1 system decreases when the mass flux is more than 0.025 kg·m −2 ·s −1, while the power output of the other connection modes increases as the mass flux increases. (2) The heat gain of the water in the N  = 1 system decreases when the mass flux is more than 0.02 kg·m −2 ·s −1 . The heat gain of the water in the N  = 2 increases continuously as the mass flux increases. However, the curve of the heat gain of water shows some volatility when the mass flux is more than 0.025 kg·m −2 ·s −1 for N  = 3, 4, and 6, and the tendency of the volatility is more obvious when the radiation is less sufficient. (3) According to the optimization index of annual actual combined electrical energy, the optimum connection mode and the optimum mass flux are N  = 2 and 0.035 kg·m −2 ·s −1, respectively.